Advancing gender equality through sustainability systems (webinar) - Bioversity International and International Center for Tropical Agriculture; ISEAL (2024)
Achieving gender equality in supply chains remains a significant challenge. Although organisations and initiatives worldwide have committed to promoting gender equality, turning these commitments into concrete actions is still a work in progress.